2011
DOI: 10.1111/j.1651-2227.2011.02509.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients with univentricular heart in early childhood: parenting stress and child behaviour

Abstract: Hypoplastic left heart syndrome, a severe congenital heart defect, increases parenting stress. The reported emotional maladjustment in affected children might in part be owing to somatic complaints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 27 publications
1
39
0
Order By: Relevance
“…Indeed, a recent study identified higher levels of stress in parents of children with HLHS compared with parents of children with other univentricular heart defects (32). Indeed, a recent study identified higher levels of stress in parents of children with HLHS compared with parents of children with other univentricular heart defects (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a recent study identified higher levels of stress in parents of children with HLHS compared with parents of children with other univentricular heart defects (32). Indeed, a recent study identified higher levels of stress in parents of children with HLHS compared with parents of children with other univentricular heart defects (32).…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties for parents, arising in PICU, may continue well after their child's discharge (11,16,27,(29)(30)(31)(32). Difficulties for parents, arising in PICU, may continue well after their child's discharge (11,16,27,(29)(30)(31)(32).…”
mentioning
confidence: 99%
“…Sarajuuri et al [20] assessed perceptions of child behavior and parenting stress among the parents of young children with HLHS and other forms of single-ventricle CHD. Sarajuuri et al [20] assessed perceptions of child behavior and parenting stress among the parents of young children with HLHS and other forms of single-ventricle CHD.…”
Section: Perform Surveillancementioning
confidence: 99%
“…Carlo et al [33] found patients who died or required transplant between S2P and Fontan completion were more likely to have a low weight for age z-score (WAZ) at S2P. Various researchers have demonstrated a high level of parental stress in households of single-ventricle children, especially at the time of initial hospital discharge [35,36]. Ensuring normal infant growth has become a priority of HMP management, and is the primary aim of the initial quality improvement goal of the ].…”
Section: Beyond Survival: Growth Feeding and Family Impactmentioning
confidence: 99%